Slow and fast slip events near the stability transition from laboratory experiments and numerical simulations - Mele Veedu, Deepa (Nanyang Technological University, 2019)
Theoretical studies establish a stability criterion for the frictional instabilities. However, how the transition from slow to fast ruptures takes place is not fully understood. Here, I investigate the unique fault behaviour around the stability criterion in numerical and laboratory experiments. In the first study, I simulate sequences of alternating slow and fast ruptures on the same patch to explain the unique recurrence pattern of the period-doubling Parkfield tremors along the San Andreas Fault. Second, I systematically investigate the physical parameters that control the inter-event times of the slow-fast ruptures. I extend the criterion for instabilities from a simple threshold to a finite transition zone characterized by slow-slower and slow-fast events. Finally, I study the slow-fast phenomena in the laboratory using granular quartz samples to compare the bifurcation pattern to that predicted numerically. Overall, these findings provide a theoretical framework to understand the physical conditions of plate boundaries that host standalone quasiperiodic slow slip and bimodal slow-fast ruptures.